2022
DOI: 10.48550/arxiv.2203.08999
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Aemulus Project V: Cosmological constraint from small-scale clustering of BOSS galaxies

Abstract: We analyze clustering measurements of BOSS galaxies using a simulation-based emulator of two-point statistics. We focus on the monopole and quadrupole of the redshift-space correlation function, and the projected correlation function, at scales of 0.1 ∼ 60 h −1 Mpc. Although our simulations are based on wCDM with general relativity (GR), we include a scaling parameter of the halo velocity field, γ f , defined as the amplitude of the halo velocity field relative to the GR prediction. We divide the BOSS data int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
19
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 92 publications
8
19
0
Order By: Relevance
“…However, there is still some disagreement amongst the small-scale analyses despite a qualitative agreement in favoring a low 𝑓 𝜎 8 relative to Planck. Our results are statistically consistent with all other small-scale analyses except for the highest redshift bin of Zhai et al (2022), which finds a particularly low 𝑓 𝜎 8 that is in ∼ 2.9𝜎 tension with our results. A full exploration of this disagreement is beyond the scope of this paper, but is necessary to ensure small-scale simulation-based analyses account for all the necessary systematics.…”
Section: Comparison To Existing 𝑓 𝜎 8 Constraintssupporting
confidence: 92%
See 2 more Smart Citations
“…However, there is still some disagreement amongst the small-scale analyses despite a qualitative agreement in favoring a low 𝑓 𝜎 8 relative to Planck. Our results are statistically consistent with all other small-scale analyses except for the highest redshift bin of Zhai et al (2022), which finds a particularly low 𝑓 𝜎 8 that is in ∼ 2.9𝜎 tension with our results. A full exploration of this disagreement is beyond the scope of this paper, but is necessary to ensure small-scale simulation-based analyses account for all the necessary systematics.…”
Section: Comparison To Existing 𝑓 𝜎 8 Constraintssupporting
confidence: 92%
“…The authors analyzed the small-scale RSD of a small sample of BOSS LOWZ LRGs and found constraints competitive with other small-scale analyses, while including a concentration-based prescription of secondary bias. Zhai et al (2022) and Chapman et al (2021) respectively analyzed the small-scale clusteirng of BOSS and eBOSS LRGs with an emulator built on the A simulation suite (DeRose et al 2019).…”
Section: Comparison To Existing 𝑓 𝜎 8 Constraintsmentioning
confidence: 99%
See 1 more Smart Citation
“…( 35) and the fact that the Hubble constant was not explicitly varied in our analysis, but was rather derived from a fixed θ 17 . This is also the case when attempting to compare against recent BOSS analyses using emulators of the redshift-space power spectrum [126] or the correlation function [90,119], with the additional difference that the correlation function analyses focused on much smaller scales than the ones we worked with. It should be also noted that the 1σ errors reported above are purely statistical, since we did not attempt to quantify how the various systematics and approximations adopted by our analysis would affect the final results.…”
Section: Resultsmentioning
confidence: 99%
“…[90] for a recent BOSS re-analysis using an ABACUS-trained emulator), the construction of an actual WST emulator will soon be possible in future work. Finally, we clarify that, even though a wide variety of approaches exist for a more accurate modeling of the cosmological dependence of the galaxy power spectrum or correlation function (e.g., perturbation theory [20, 76-78, 109, 110]) or emulators [90,103,[117][118][119]), we use the model from Eq. ( 35) for the power spectrum, as well, in order to guarantee a fair comparison against the performance of the WST, which is the ultimate purpose of this work.…”
Section: E Likelihood Analysismentioning
confidence: 99%